Nursing Home Resident Symptomatology Triggering Transfer: Avoiding Unnecessary Hospitalizations - Alyce S. Ashcraft; Jane Dimmitt Champion (Nursing Research and Practice)
The purpose of this study was to describe nursing home resident symptomatology and medical diagnoses associated with nursing home to hospital transfers. A retrospective chart review of documented transfers was conducted at a 120-bed, nonprofit urban Continuing Care Retirement Center nursing home facility located in the southwestern United States. The transferred residents (n=101) had seventy different medical diagnoses prior to hospital transfer with hypertension, coronary artery disease, and congestive heart failure most frequently reported. Most frequently reported symptomatology included fatigue, lethargy or weakness, shortness of breath, and change in level of consciousness. Multiple symptomatology was indicative of a wide variety of medical diagnoses. The diagnoses and symptomatology recorded in this paper identify the importance of strategic planning concerning assessment and communication of common nursing home resident symptomatology and the importance of basic nursing and diagnostic procedures for prevention of potentially avoidable hospitalizations.